HIV- and AIDS-related knowledge and attitude of residents in border regions of Vietnam - Canh Dinh Hoang; Bach Xuan Tran; Manh Duc Pham; Long Hoang Nguyen; Ha Ngoc Do; Quan Hoang Vuong; Manh Tung Ho; Van Nhue Dam; Thu Trang Vuong; Hai Hong Nguyen; Vu Nguyen; Hai Quang Pham; et al. (BMC, 2019)
Abstract Background Residents in border areas are vulnerable to HIV/AIDS due to high rates of risk behaviors such as unprotected sexual practices or illicit drug use. Improving knowledge and attitude toward HIV/AIDS prevention and treatment are vital to diminish the burden of the HIV epidemic in this setting. However, evidence about this issue in Vietnam has been limited. This study aims to explore the knowledge and attitude toward HIV/AIDS among people in Vietnam border zones. Methods We conducted a cross-sectional study in three border communes in Thanh Hoa province with 600 HIV(−) residents. Data about socio-demographic characteristics, general HIV knowledge, knowledge about prevention of mother-to-child transmission, treatment and care, HIV testing services, and attitude toward HIV/AIDS were collected. Multivariate Tobit regression was used to determine related factors with the knowledge and attitude. Results The highest percentage of people having correct statements was for "HIV could be transmitted from mother to child" (98.2%), while the lowest percentage was for item "Know health facilities where HIV-positive people could register for care and check-up" (28.2%). People had the highest score in "Knowledge about HIV transmission routes" and the lowest score in "Knowledge about HIV/AIDS prevention measures". Most of the people were not afraid of being exposed to HIV-positive individuals (66.0%), willing to buy goods from HIV-positive sellers (78.9%), and willing to take care of people living with HIV in their family (90.1%). Education, ethnic, marital status, occupations, and HIV/AIDS information sources were found to be associated with knowledge and attitude toward HIV/AIDS. Conclusions The general knowledge and attitude on HIV/AIDS of residents were relatively good. Educational campaigns to improve knowledge and attitude toward PLWH, involving peer educators and local associations, are potential strategies for sustaining HIV intervention in this remote setting.